The Application of A Saprahan-Based Economic Learning Model in Senior High School of Sambas District - Muhammad Basri (STKIP Singkawang, 2024)
The purpose of this study is to evaluate a saprahan-based economic learning paradigm for Sambas Regency high school students. This study employed a quasi-experimental design and a quantitative methodology. Six schools comprising 66 pupils served as the research participants. This study's data analysis employed the Wilcoxon non-parametric t-test. The saprahan-based economic learning model successfully improved the students' economic learning outcomes, as evidenced by the statistical tests using Wilcoxon that showed a significant difference (increase) in the learning outcomes between the pre-test and post-test findings.